Macromolecular composition of terrestrial and marine organic matter in sediments across the East Siberian Arctic Shelf; The Cryosphere; Vol. 10, iss. 5 - Sparkes R. B. Robert; Selver A. D. Ayca Dogrul; Gustafsson O. Orjan; Semiletov I. P. Igor Petrovich; Haghipour N. Negar; Wacker L. Lucas; Eglinton T. Timothy; Talbot H. M. Helen; Van Dongen B. E. Bart (2016, 2016)
Title screen